Pregnant mothers’ awareness about the anti-hiv test during prenatal care visits - Moreira, Karla de Abreu Peixoto; Braga, Lígia de Oliveira; Vieira, Ângela Maria Leal de Moraes; Queiroz, Maria Veraci Oliveira (Rev Rene, 2006)
The AIDS epidemic is affecting more and more women of fertile age. However, taking the HIV test is an important strategy to reduce the morbid mortality for such cause. The aim of this study was to investigate pregnant women’s awareness of the importance of taking the HIV test during the pre-natal period. The study sample consisted of 50 pregnant mothers who were undergoing low-risk pre-natal exams without confirmed diagnosis of AIDS. They were basically between 20 to 25 years of age. Most of them had already been questioned in previous visits to the hospital about the importance of the HIV test and 92% had confirmed that they had taken the test after the first prenatal care visit. It is important to restate the importance of health education concerning prevention and control of AIDS.